Soya for the sick - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Mercy Chavula of the Orphan and Home Based Care Committee in Kuntaja traditional authority, Blantyre, Malawi, explains the benefits of growing soya, a highly nutritious crop which is having a major impact on the health of children and the sick in her comm